(untitled) (Nigerian Journal of Technology, 2020)
The study investigated the influence of temperature difference (?T) between evaporative and condensing surface temperature on water productivity of hemispherical solar still. The still was developed, tested and evaluated under the climatic conditions of Ile-Ife, Nigeria, to obtain an average distillate yield per hour per day for different combination of basin temperature, water temperature, transparent cover temperature, ambient temperature and solar intensity. Results indicated a decrease in the hourly water yield as (?T) increases. Regression analysis revealed that ?T has no significant influence on the hourly water yield (P > 0.05). Maximum water productivity was obtained for a low condensing surface temperature and a high evaporative surface temperature. The study concluded that the improvement on water productivity of solar still can be achieved by enhancing the evaporative and condensing surface temperature. Methods for obtaining higher evaporating temperature should be sought in order to boost water productivity of solar stills. http://dx.doi.org/10.4314/njt.v39i3.19